KAJIAN EPISTEMOLOGI BARAT Telaah Epistemologi Barat Fenemonelogi Hermeneutika dan Kritis: Telaah Epistemologi Barat Fenemonelogi Hermeneutika dan Kritis - Abdul Rohman, Moch (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2023)
This paper examined the Western epistemology thought. The theme focuses on Plato to Gonseth thought. The Epistemology that referred in this article, is to think about" how humans acquire knowledge?". From this then appears four types of sect modern western epistemology thought, namely: sect of empiricism, rationalism sect, kantinian sect, sect of positivism. Furthermore, the social positivism sciences developed by Comte leaves serious problems associated with the loss of the role of the subject. This problem being the background of epistemology philosophy appears that by Emund Husserl developed through the phenomenology, Habermas through hermeneutics, and Ferdinand Gonseth through critical theory.